Instructions on the Use of Unmanned Aerial Vehicles (UAVs) - Sri Charan Kakarla; Yiannis Ampatzidis (EDIS)
The purpose of this document is to provide guidance on the appropriate use of Unmanned Aircraft Vehicles (UAV) or Unmanned Aircraft Systems (UAS) in the State of Florida. All research and commercial activities involving the use of UAVs shall be conducted in compliance with applicable federal and state laws, statutes, and regulations. The Federal Aviation Administration (FAA) has jurisdiction over all navigable airspace in the United States. All aircraft, whether manned or unmanned, are subject to FAA rules and regulations and violations carry severe federal penalties.